“Wading through the worst that humanity does to each other”: New Zealand Crown prosecutors’ experiences of working with potentially traumatic material in the criminal justice system - Kim, Rachel; Tyler, Nichola; Tinsley, Yvette (Frontiers in Psychology, 2023)
Occupational exposure to trauma and its potential impacts on legal professionals working in the criminal justice system is an area that has historically been neglected and has only gained traction in recent years. Crown prosecutors, as a subset of practising criminal lawyers in New Zealand, are arguably at heightened risk of vicarious trauma (VT) due to their occupationally distinct exposure to potentially traumatic material (PTM). However, no research to date has explored the experiences of this group of working with PTM. This qualitative study aimed to explore New Zealand Crown prosecutors’ experiences of working with PTM. Nineteen Crown prosecutors from four Crown Solicitor firms across New Zealand participated in individual semi-structured interviews. The data was analysed using reflexive thematic analysis (Braun & Clarke, 2006, 2013). Three themes were developed that described Crown prosecutors’ experiences of work-related exposure to trauma: trauma is everywhere, enduring effects of PTM exposure, and coping in the moment. These findings add to the growing body of literature on legal professionals’ work-related wellbeing and highlights how they are an at-risk population for VT, which can be significant and enduring. Further research is needed to understand the unique etiological pathways for both the consequences of working with PTM and effective ways to reduce this occupational risk for legal professionals working in the criminal law.